Serosurvey of spotted fever group Rickettsia in equids from western Pará, Amazon, Brazil (2022)
From a previous large epidemiological survey, we randomly selected 474 serum samples (463 horses and 11 mules) distributed among four municipalities of Pará state, Amazon region, Brazil, and from three types: farm animal, urban carthorse, and sport horse. Samples were tested by indirect fluorescence antibody test (IFAT ≥ 64) for antibodies reactive to spotted fever group (SFG) rickettsiae using Rickettsia rickettsii as crude antigens. From the 474 equids tested, 149 (31.4%) had ticks attached during sampling, belonging mostly to the species Dermacentor nitens. The overall seroprevalence for SFG rickettsiae was 31.4% (95% confidence interval: 27.3–35.9%) with 149 seropositive animals out of 474 screened. Notably, 77 equids (16.2%) had high endpoint titers ranging from 512 to 16,384, indicating that they had been exposed to SFG rickettsiae not long before sampling. Animal type affected rickettsial seroprevalence, with significantly higher values among farm horses when compared with urban and sport animals. Presence of dogs and tick infestation were negatively associated with equid seropositivity to R. rickettsii. This is the first report of SFG rickettsiae-reactive antibodies in equids from Pará state, Brazilian Amazon.